1989
DOI: 10.1177/0145482x8908300904
|View full text |Cite
|
Sign up to set email alerts
|

The Preschool Blind ChildCanBe a Cane User

Abstract: Teaching blind, preschool-age children to use a long cane in travel is a relatively new concept in orientation and mobility. This article examines this issue and discusses potential advantages of early cane use, challenging traditional arguments against early introduction of the cane. Instructional considerations and optional strategies for teaching use of the cane to preschoolers are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…We did not find this to be the case in our study. Postural abnormalities that were described by Pogrund and Rosen (1989) may be explained by the compensatory strategies used by individuals with visual impairments. However, an important consideration, based on the results of our study, is that individuals with visual impairments tend to use a hip strategy for balance, rather than the preferred ankle strategy.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…We did not find this to be the case in our study. Postural abnormalities that were described by Pogrund and Rosen (1989) may be explained by the compensatory strategies used by individuals with visual impairments. However, an important consideration, based on the results of our study, is that individuals with visual impairments tend to use a hip strategy for balance, rather than the preferred ankle strategy.…”
Section: Implications For Practicementioning
confidence: 99%
“…Skaggs and Hopper (1996) noted that people with visual impairments use the proprioceptive senses as a substitute for vision when they complete balance tasks, and Bouchard and Tetreault (2000) reported that adolescents with visual impairments have inadequate static balance. Furthermore, Sleeuwenhoek, Boter, and Vermeer (1995) reported that individuals with visual impairments walk stiffly and hesitantly and demonstrate balance difficulties, and Pogrund and Rosen (1989) indicated that people who are congenitally blind demonstrate postural anomalies, especially a backward lean of the trunk. In older adults with visual impairments, the loss of balance and mobility presents a barrier to independence that is associated with the fear of falling (Crews & Campbell, 2001;Maeda et a1., 1998).…”
mentioning
confidence: 99%
“…Orientação e Mobilidade (OM) é o processo que proporciona ao aluno cego as condições de se situar no meio físico em que vive, se movimentar livremente, explorar os objetos que o cercam, adquirir a autonomia e a independência social (FARIAS, 2000). O objetivo da OM é possibilitar, ao máximo, a autonomia e a independência do indivíduo, esclarecem Pogrund & Rosen (1989). Por que, por exemplo, não desafiar as crianças cegas do estudo a participarem do JO?…”
Section: Introductionunclassified
“…Portadores de deficiência visual apresentam alterações, tais como diminuição da velocidade da marcha, 8-10 do comprimento de passo, 8,11 da cadência, 10 da fase de balanço 10 e do ângulo de extensão do quadril durante a fase de impulso, 11,12 bem como aumento da duração da fase de apoio, 8 ausência do contato inicial com o calcanhar no solo, sendo substituído por toda planta do pé, 11,13 e acentuação da rotação externa do quadril. 13 Embora já existam algumas evidências relacionadas à diferença entre a marcha de portadores de deficiência visual e indivíduos de visão normal, poucos estudos Nakamura et al 8 referentes ao assunto são encontrados na literatura, principalmente na população de cegos do Brasil. Dessa forma, a mensuração da marcha em indivíduos cegos, poderia auxiliar na caracterização deste movimento e consequentemente no desenvolvimento de estratégias para a prevenção de possíveis alterações, ou para promoção da reabilitação da marcha nessa população.…”
Section: Introductionunclassified